Accounting students' perceptions: Internal control theory moves outside the classroom and online - Sexton, N.D. (South African Journal of Higher Education, 2019)
Many have argued that faculty should transform the way accounting programmes are presented to undergraduate students. Changes in student expectations, professional qualifications and employer demands have driven innovative experiential learning interventions. Students want to learn collaboratively, inside and outside of the classroom, they want to use information technology and have fun. In response, this article reports on an auditing assignment where students were required to identify control weaknesses in everyday life, record it and report back using Facebook. A Facebook group was created where students posted photos or videos of the control weakness they identified. Other students could “like,” comment and share posts. This was the first assignment of this nature. This research presents the accounting students’ perceptions of the assignment as a whole, the pervasive skills applied and the use of Facebook. These were generally positive and should encourage educators to keep integrating technology and real life into learning.